Tensões críticas e culturais em Rilke shake de Angélica Freitas - Hayashi, Gabriel José Innocentini (2014)
The object of this dissertation is the book of poems Rilke shake, by Angelica Freitas, and the main question that guided our research was: What are the critical and fundamental cultural issues that inform Angelica Freitas s poetical production in Rilke shake? With this question in mind two objectives were followed: a) to accomplish the reading and analysis of the poems and b) to discuss how the tensions between the poetic tradition and the contemporary world are articulated in the poems. These two objectives were interrelated and linked to enable us to create an interpretative key of Rilke shake. Angelica Freitas establishes a dialogue with European, North American and Brazilian modernist traditions and her work shows a belonging to the post-modern world. Eight Poems from the book were discussed in the attempt at investigating which elements indicate such a dialogue. The cultural system in which Freitas s work takes part and constitutes one of the representative examples was then discussed. Our aim was to show that discussing Rilke shake meant also discussing how contemporary critical thinking looks at contemporary poetry, setting the dialectical movement from the particular to the general and back. The systemic approach offers the reader a larger view, allowing him to understand the importance and the value of Rilke shake inside the discussions concerning contemporary poetry.